The Enigmatic Sutton Hoo Ship-Burial: Fresh Insights from Assemblage Theory. - Pitt, Georgina (Parergon, 2019)
The sumptuous Sutton Hoo ship-burial has been much debated since it was discovered nearly eighty years ago, but there is no consensus on its interpretation. Assemblage theory, with its focus on the linkages between people, places, and objects, and the related concept of 'fittingness', may provide an alternative explanation which accounts for this ship-burial as both archaeological site and historical event. I suggest that this ship-burial was a deliberate strategy to cohere and transmit secular political power across the hazardous liminal space between death and succession in troubled times in early seventh-century East Anglia, after the death of King Rædwald.